2017
DOI: 10.1371/journal.pntd.0005825
|View full text |Cite
|
Sign up to set email alerts
|

Control of chronic Strongyloides stercoralis infection in an endemic community may be possible by pharmacological means alone: Results of a three-year cohort study

Abstract: ObjectivesTo assess the effect of treatment with ivermectin on the prevalence of S. stercoralis infection in an Australian Aboriginal population over a three year period, and to assess the validity of using a lower ELISA cut-off in diagnosis.MethodsA three-year cohort study of 259 adult Australian Aboriginals living in a remote community in northern Australia. S stercoralis infection was diagnosed using commercial ELISA testing, and employed a lower threshold for treatment than that recommended. Follow up was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…Another study in tropical Australia demonstrated that after treatment with ivermectin there was a sustained decrease in the rates of S. stercoralis seropositivity at 3 years of follow-up. 7 Other studies have found similar results. 8,9 This suggests that addressing the human reservoir may lead to lasting benefits for the general population and indicates that with effective programs aimed at S. stercoralis infection, elimination may be an attainable goal.…”
supporting
confidence: 52%
“…Another study in tropical Australia demonstrated that after treatment with ivermectin there was a sustained decrease in the rates of S. stercoralis seropositivity at 3 years of follow-up. 7 Other studies have found similar results. 8,9 This suggests that addressing the human reservoir may lead to lasting benefits for the general population and indicates that with effective programs aimed at S. stercoralis infection, elimination may be an attainable goal.…”
supporting
confidence: 52%
“…Nevertheless, the testing used is validated and established for diagnosis of S. stercoralis infections and prevalence studies 9 . A further important issue is that the anthelmintic effect of ivermectin treatment to prevent Strongyloides hyperinfection syndrome in untreated seropositive patients was not the subject of this study, there is however established evidence to support its use 28 , 29 . Finally, the retrospective design of the study limited the analysis due to predesigned study conditions and therefore availability of selectively preserved samples.…”
Section: Discussionmentioning
confidence: 98%
“…Both ‘test‐and‐treat’ and mass drug administration strategies have been shown to dramatically reduce the prevalence of strongyloidiasis in communities . Environmental strategies include ensuring access to adequate sanitation and housing and appropriate animal control and treatment …”
Section: Discussionmentioning
confidence: 99%
“…Answer: e. All of the above interventions have been incorporated into successful community‐based programmes that have demonstrated reductions in the seroprevalence of strongyloidiasis in remote Indigenous communities in Australia …”
Section: Multiple Choice Questionsmentioning
confidence: 99%